(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
Imperatives of constructing the Memory, restoring the Truth and rendering Justice to the victims of human rights violations committed during the Argentine civic-military dictatorship (1976-1983) are the main theme of this article, which traces the attitudes of the governments that succeeded one another from the transition to democracy, launched by the Radical leader Raúl Alfonsín in 1983, to the present day. Particular attention is paid to the contribution of Kirchnerism (2003-2015), to the position of the Macrist conservative government (2015-2019) and, finally, to the early initiatives of Peronist president Alberto Fernández, who took over the presidency on 10 December 2019.